Pharmacological characterization of cnidarian extracts from the Caribbean Sea: Evaluation of anti-snake venom and antitumor properties - Oliveira, Cláudia S.; Caldeira, Cleópatra A.S.; Diniz-Sousa, Rafaela; Romero, Dolores L.; Marcussi, Silvana; Moura, Laura A.; Fuly, André L.; de Carvalho, Cicília [UNESP]; Cavalcante, Walter L.G. [UNESP]; Gallacci, Márcia [UNESP]; Pai, Maeli Dal [UNESP]; Zuliani, Juliana P.; et al. (Springer Nature, 2018)
Background: Cnidarians produce toxins, which are composed of different polypeptides that induce pharmacological effects of biotechnological interest, such as antitumor, antiophidic and anti-clotting activities. This study aimed to evaluate toxicological activities and potential as antitumor and antiophidic agents contained in total extracts from five cnidarians: Millepora alcicornis, Stichodactyla helianthus, Plexaura homomalla, Bartholomea annulata and Condylactis gigantea (total and body wall). Methods: The cnidarian extracts were evaluated by electrophoresis and for their phospholipase, proteolytic, hemorrhagic, coagulant, fibrinogenolytic, neuromuscular blocking, muscle-damaging, edema-inducing and cytotoxic activities. Results: All cnidarian extracts showed indirect hemolytic activity, but only S. helianthus induced direct hemolysis and neurotoxic effect. However, the hydrolysis of NBD-PC, a PLA2 substrate, was presented only by the C. gigantea (body wall) and S. helianthus. The extracts from P. homomalla and S. helianthus induced edema, while only C. gigantea and S. helianthus showed intensified myotoxic activity. The proteolytic activity upon casein and fibrinogen was presented mainly by B. annulata extract and all were unable to induce hemorrhage or fibrinogen coagulation. Cnidarian extracts were able to neutralize clotting induced by Bothrops jararacussu snake venom, except M. alcicornis. All cnidarian extracts were able to inhibit hemorrhagic activity induced by Bothrops moojeni venom. Only the C. gigantea (body wall) inhibited thrombin-induced coagulation. All cnidarian extracts showed antitumor effect against Jurkat cells, of which C. gigantea (body wall) and S. helianthus were the most active; however, only C. gigantea (body wall) and M. alcicornis were active against B16F10 cells. Conclusion: The cnidarian extracts analyzed showed relevant in vitro inhibitory potential over the activities induced by Bothrops venoms; these results may contribute to elucidate the possible mechanisms of interaction between cnidarian extracts and snake venoms.
Keywords: Antiophidic; Antitumor; Bioprospection; Caribbean sea cnidarians; Natural products